Pension Reform in China : The Need for a New Approach - Dunaway, Steven (IMF Working Papers; Working Paper ;, 2007)
The rapid aging of China's population over the next few decades makes it important for a new pension system with broad and adequate coverage to be put in place quickly. Pension reforms, first initiated in 1997, have become bogged down in difficulties over dealing with the "legacy costs" associated with the relatively more generous benefits provided under the old system. This paper argues that a way forward is to separate the legacy problem from the problem of setting up a new pension system, and it suggests concrete proposals for setting up such a new system which would cover both urban and rural workers.